Intersections of Personal and Professional Morality: Reconsidering Ethical Responsibility in Professional Practice (Jagannath University Journal of Arts, 2026)
Professional and personal ethics are two essential dimensions in applied ethics that are considered crucial for building trust, improving decision-making, and establishing individual and professional reputations. However, there is a substantial gap in the literature and an intellectual debate on the intersection of personal and professional morality in the context of professional practice. This paper examines the relationship between individual and professional morality, illustrating how their interaction affects ethical decision-making, responsibility, and moral identity within the professional context. It argues that moral conduct in professional settings should be based on the combination of personal values, professional norms, and collective responsibilities, rather than solely on a single entity. Utilising a collective moral responsibility framework, this paper delves into detail on how ethical conduct is often the result of a shared decision-making process and systematic influences of morality. It also uncovers diverse situations where personal convictions conflict with professional responsibilities, and institutional structures either enable or inhibit moral agency. This paper recommends rethinking professional ethics as a multi-layered moral framework that unites self-reflective moral judgment, professional commitment, and collective accountability. This framework not only prevents moral disengagement but also strengthens moral credibility and public trust essential to all professional communities.Jagannath University Journal of Arts, v-15, i-2, 2025:p119-127